2020
DOI: 10.3390/electronics10010043
|View full text |Cite
|
Sign up to set email alerts
|

Context-Aware and Occlusion Handling Mechanism for Online Visual Object Tracking

Abstract: Object tracking is still an intriguing task as the target undergoes significant appearance changes due to illumination, fast motion, occlusion and shape deformation. Background clutter and numerous other environmental factors are other major constraints which remain a riveting challenge to develop a robust and effective tracking algorithm. In the present study, an adaptive Spatio-temporal context (STC)-based algorithm for online tracking is proposed by combining the context-aware formulation, Kalman filter, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Some potential ideas should be considered. (1) The idea of adaptive spatial-temporal context [33] can be used to improve the robustness of the tracking part in the TBD. (2)The multi-sensor data fusion [34,35] may be a valuable project for theoretical investigation and practical application in the dim point detection field.…”
Section: Discussionmentioning
confidence: 99%
“…Some potential ideas should be considered. (1) The idea of adaptive spatial-temporal context [33] can be used to improve the robustness of the tracking part in the TBD. (2)The multi-sensor data fusion [34,35] may be a valuable project for theoretical investigation and practical application in the dim point detection field.…”
Section: Discussionmentioning
confidence: 99%
“…A Kalman filter is used in various tracking algorithms for occlusion handling [45][46][47][48][49]. Kaur et al [50] suggested a real-time tracking approach using a fractional-gain Kalman filter for nonlinear systems.…”
Section: Related Workmentioning
confidence: 99%
“…Visual object tracking [ 1 , 2 ] is widely used in autonomous driving, medical diagnostics, traffic monitoring, and other fields. Visual tracking aims at estimating the position and scale of the object in subsequent frames, given its state in the first frame.…”
Section: Introductionmentioning
confidence: 99%